Risk of early impaction of maxillary canines using panoramic radiographs - Cueva Buendía , Luis Alberto (2024)
Objective: Determine the risk of impaction of maxillary canines in children between 8 and 11 years old in a radiological center in Huancayo according to the Power and Short method. Material and Methods: Basic study of cross-sectional descriptive design. Non-parametric tests, Kruskal-Wallis Kruskal-Wallis to find significant differences between angulation values by age and sex of the patients. between angulation values according to age and sex of the patients; and Friedman to find significant differences to find significant differences between angulation values according to the quadrant involved. quadrant involved. Results: According to gender were that females have a higher unfavorable risk of impaction with 3.9%, regular 15.2 and favorable 35.8%; unfavorable male gender was 0.9%, regular 11.8% and favorable 32.4%; According to age, the proportion of favorable risk was highest in the age group of 11 years with 29%, in 9 years 15.1%, in 10 years 12.7%, in 8 years 11.2%; The regular risk was majority in the 11-year-old group with 14.7%, 6.8% in 8 years, 5.8% in 9 years and 1.4% in 10 years; the unfavorable risk in 11 years was 3.4% and in 10 years; 9 and 8 years old have 0.4% each. Conclusions: The risk of impaction of the maxillary canines was favorable in 68.2%, regular in 27% and unfavorable in 4.8%. There was no significant difference between the angulations according to the right and left quadrants, according to age or sex. (p-value of 0.89 and 0.20 respectively)